Plasma homoarginine concentrations in ewe's pregnancy and association with the number of fetuses. (May 2022) - Sotgia, Salvatore; Berlinguer, Fiammetta; Porcu, Christian; Pasciu, Valeria; Molle, Giovanni; Dattena, Maria; Gallus, Marilia; Bassu, Stefania; Mangoni, Arduino A.; Carru, Ciriaco; Zinellu, Angelo
Abstract: A striking increase in homoarginine concentrations, about more than 100-fold that observed in humans, was recently reported during pregnancy in a nutritionally induced model of intra-uterine growth restriction in ewes. To determine whether this phenomenon is at least partially related to the nutritional regimen, estrus synchronization, or analytical method, thirty-four one-year-old primiparous, non-synchronized, and well-fed Sarda breed ewes were exposed to fertile rams allowing those who came into estrus to naturally mate. Plasma arginine, homoarginine, asymmetric dimethylarginine, symmetric dimethylarginine, mono methylarginine, and citrulline concentrations were measured in each sample using LC-MS/MS. Homoarginine concentrations showed a 44-fold variation between the highest and the lowest values while the fluctuations of arginine and its analogues and metabolites were much smaller, between 1.1 and 1.6-fold. Repeated-measures correlation analysis showed a significant negative correlation between homoarginine/arginine and arginine/asymmetric dimethylarginine ratios (Rm = −0.40; P < 0.000001). Furthermore, median homoarginine concentrations significantly increased with the number of fetuses. The marked increase in homoarginine concentrations with advancing gestational age is genuine and independent of mating, feeding, diet, and hormone treatment. The higher homoarginine concentrations found in ewes bearing multiple fetuses suggest the presence of a physiological link between this arginine analog and energy metabolism in pregnancy that warrants further investigation. Highlights: Plasma L-homoarginine concentrations in ewe's pregnancy are more than 100-fold that reported in humans. The increase of L-homoarginine with gestational age is independent of mating, feeding, diet, and hormone treatment. The sharing of a metabolic pathway with creatine links L-homoarginine to energy metabolism.